A Ruppert’s framework: How do prospective teachers develop analogical reasoning in solving algebraic problems? - Lailiyah, Siti; Kusaeri, Kusaeri; Retnowati, Endah; Erman, Erman (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2022)
It is widely agreed that knowing how prospective teachers develop analogical reasoning in solving problems is essential. Problem solving is specific domain that requires particular ways of analogical reasoning skill. The purposes of this study was to reveal the development of analogical reasoning and strategies used bya porspective teachers. The research design used a qualitative method. As many as sixty nine mathematics prospective teachers were involved voluntarily to complete algebraic tasks and 12 of them were interviewed to investigate their analogical reasoning and solution strategies. The data analysis used Ruppert’s framework consisting of four components: structuring, mapping, applying, and verifying. It was found that the first three components were fully performed by the prospective teachers. However, the verifying stage was applied by prospective teachers in different ways. The dominant strategy used was a combined multiplication and addition. Their strategies varied according to the participants’ general ability. The more strategies employed in solving problems, the better their analogical reasoning is becomes. This implies that instructional designs that will be developed by prospective teachers may vary. Therefore, during their candidature, they should be provided with many solving strategies in problem-solving to develop students’ analogical reasoning.